Advanced Colloidal Sensors Enabled by an Out‐of‐Plane Lattice Resonance. Issue 11 (7th September 2022) - Gupta, Vaibhav; Aftenieva, Olha; Probst, Patrick T.; Sarkar, Swagato; Steiner, Anja M.; Vogel, Nicolas; Fery, Andreas; König, Tobias A. F.
Abstract : The rational design and dispersion engineering of plasmonic colloid gratings are mainly responsible for advancing refractive index sensors. Herein, a 1D colloidal plasmonic lattice composed of nanoparticle dimer chains fabricated by a combination of interference lithography, soft molding, and colloidal self‐assembly is studied. The bottom‐up approach affords centimeter‐scale arrays of high‐quality colloidal nanoparticles with resonances in the visible range. Demonstrating a special case of collective plasmonic coupling called out‐of‐plane lattice resonance (OPLR) is focused on. Such OPLRs are excited, solely under oblique illumination with transverse magnetic polarization, and these findings with electromagnetic simulations are supported. In addition, it is experimentally found that such resonances are spectrally narrow with a linewidth of 8.08 ± 0.6 nm and have a quality factor of 78.49 ± 5.7, an enhancement by a factor of 11.62 compared with a single particle. The oblique incidence provides field enhancement outside the substrate plane, which is more accessible and sensitive to a surrounding analyte. A simple glycerol–water mixture as a model system to demonstrate this enhanced sensitivity and discuss the potential for a sensing application in an asymmetric refractive index environment is demonstrated. Beyond these sensing applications, this platform has the potential to enhance other processes, such as hot carrier injection or coherent energy transfer. Abstract : A 1D colloidal plasmonic lattice composed of nanoparticle dimer chains fabricated by a combination of interference lithography, soft molding, and colloidal self‐assembly is shown. Such 1D dimer nanoparticle lattices demonstrate narrow out‐of‐plane lattice resonances (OPLRs). Further, these OPLRs are used to create a colloid‐based flexible sensor.